Emotional Closeness Guru Dalam Menumbuhkan Motivasi Belajar Siswa Slow Learner - Astuti, Winarni Puji; Surjati, Endang; Ni’matullah, Onik Farida (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
The unpreparedness of teacher in inclusive school programs in schools can be seen from teachers are not to focus on students, the impact of this condition makes slow learners’ students less motivated in their learning. This research is qualitative research with a descriptive approach, using case studies located at UPT SMPN 7 Pasuruan, the data in this research are interview, observation, and documentation. Primary data sources were obtained from the Deputy Head of Curriculum Affairs, representative of teachers’ study, and slow learners’ students. The result of research with two research objectives, namely the learning motivation of slow learners’ students, the role and emotional closeness of teachers can foster the learning motivation of slow learners’ students. Teachers’ emotional closeness by making slow learner students friends with whom they can discuss makes students have self-confidence, teachers provide learning guidance with sincerity, so that the closeness provided is of good quality and simple caring can foster empathy and sympathy.